INFLUENCE OF GAMMA RADIATION ON EUTECTIC PHASE AREA AND HARDNESS PROPERTIES OF SAC305 SOLDER (Jurnal Teknologi (Sciences & Engineering), 2022)
Gamma radiation plays an important role in changing the properties and behavior of the materials. In this present work, the correlation between the intermetallic compound (IMC), eutectic phase area and hardness of the lead-free solder radiated with low dose gamma radiation were investigated. Using a technique known as stencil printing, the solder paste was manually applied to the printed circuit board (PCB). Subsequently, the solder PCB was reflow soldered at 260 ˚C and allowed to expose to a variation of low dose gamma radiation (5, 10, 15, 20 and 25 Gy). Prior to the indentation test, the samples were subjected to a metallographic process to examine the cross-section of the interface between the solder and the substrate. The microstructure, intermetallic compound (IMC) and hardness properties were captured and measured via optical microscope and nanoindentation test equipment respectively. The IMC thickness of the solders increased with increasing radiation exposure, suggesting that gamma radiation influenced the morphologies of the SAC305 solder, leading to a change in IMC thickness. The effect of the exposure of various doses of gamma on the phase distribution of the eutectic in the SAC305 solder was also investigated. The eutectic phase area showed a comparable trend in the value of hardness obtained. The eutectic area increased up to 29.65 % after being radiated by 15 Gy of gamma, then decreased to 17.66 % when exposed to 25 Gy. From the nanoindentation test, the load-displacement curves extracted the value of hardness of the SAC305 solder.